Design of Automatic Pond Water Quality Control in Koi Fish Farm - Muhammad Daud; Rizqan Fachroji; Arnawan Hasibuan; Raihan Putri; I Made Ari Nratha; Muzamir Isa (Institute for Research and Community Service (LPPM), Universitas Malikussaleh, Indonesia, 2023)
Koi fish is a type of freshwater ornamental fish that has high economic value. Koi fish have attractive body colors and ideal body shapes so they have good sales prospects. However, koi fish farming has several obstacles, one of which is the low recovery rate and the relatively slow growth of fish. Water quality is the main parameter in the success of a fishing effort. Therefore, this study designed a tool that can help koi fish farmers in unifying the quality of pond water so that koi fish can grow and develop properly. This monitoring system is designed by implementing an automatic control monitoring system to produce good water quality for koi fish farming. Data obtained from water quality monitoring are parameters of pH, ammonia, and water temperature. The results of this cultivator's research can monitor the quality of fish pond water and immediately get water quality control automatically.